As representações sociais da Geografia escolar: um olhar sobre a prática didático-pedagógica - Oliveira, Marlene Macário de (2006)
To present research had for study object to understand the social representations of the school geography for the students of the Municipal Schools Lions Prata and Dr. Francisco Brasileiro, located in the neighborhood of Catolé, and in Santa Terezinha District, respectively, in the municipal district of Campina Grande/PB. The objective of that study consisted of identifying, to understand and to analyze those apprehensions in the form as they are communicated and executed at the school and in the society. That search is due to the fact that the constant reproduction of the same ones in the current world context in that we are inserted doesn't to the understanding of the being's complexity and of the knowledge in the educational and social extent. Like this, we considered urgent their dialogues in practice didactic-pedagogic of the geography for ressignificar the geographical knowledge produced in the city. Authors as Moscovici; Jodelet; Bourdieu; Tuan; Foucault; Castoriadis; Morin among others contributed in the reflexive mediation of the imaginary symbolic emitted by the interior speeches of the 281 (two hundred and eighty and a) researched students. Those corresponded to 64,0% (sixty four) integral of the enrolled ones in the two schools of the municipal public system of teaching (INEP, 2005). A qualitative-quantitative survey was used and its answers were categorized by using the statistical description of the Statistical Package for the Social Sciences SPSS Program. The freeassociation of words technique was also used in order to verify some information. The results revealed that the social representations of geography are still grounded in fragmented, content-based, positivistic and functional conceptions of man, society and the world. Manifestation of a traditional and organicistic teaching, this unveiling excludes the historical capacity of the students creative construction of knowledge, as well as a competent and demanding educational mediation